World Bank East Asia and Pacific Economic Update, April 2019 : Managing Headwinds - World Bank (Washington, DC: World Bank, 2019)
Despite global economic volatility, growth in developing East Asia and Pacific (EAP) was resilient during 2018, and in the first quarter of 2019. The growth outlook for developing EAP is expected to soften in 2019, as China's economic expansion continues to moderate. Downside risks remain, including expected moderated global demand, continued trade tensions, the risk of a faster-thanexpected financial tightening in developed economies, the risk of weaker-than-expected growth in China, and continued financial market volatility. Also, or in combination, these risks could weigh on the· region's growth prospects in the short-to-medium term. To manage global and regional headwinds, developing EAP economies should reduce short-term vulnerabilities and enhance buffers, redouble their commitment to an open, rules-based international trade and investment framework, including through deeper regional economic integration, and deepen structural reforms. The intensification of risks underscores the need to continue to enhance economic security by investing in human capital and strengthen social assistance.